Cross Talk Between Natural Killer T and Dendritic Cells and Its Impact on T Cell Responses in Infections - Zhao, Lei; Yang, Xi (Frontiers in Immunology, 2022)
Both innate and adaptive immunity is vital for host defense against infections. Dendritic cells (DCs) are critical for initiating and modulating adaptive immunity, especially for T-cell responses. Natural killer T (NKT) cells are a small population of innate-like T cells distributed in multiple organs. Many studies have suggested that the cross-talk between these two immune cells is critical for immunobiology and host defense mechanisms. Not only can DCs influence the activation/function of NKT cells, but NKT cells can feedback on DCs also, thus modulating the phenotype and function of DCs and DC subsets. This functional feedback of NKT cells on DCs, especially the preferential promoting effect on CD8α+ and CD103+ DC subsets in lymphoid and non-lymphoid tissues, significantly impacts the systemic and local adaptive CD4 and CD8 T cell responses in infections. This review focuses on the two-way interaction between NKT cells and DCs, emphasizing the importance of NKT cell feedback on DCs in bridging innate and adaptive immune responses for host defense purposes.